Effect of Scientific Discovery Learning on Critical Thinking in Biology Education Students - Nurmiati Nurmiati; Jirana Jirana; Nenny Indrawati; Mesra Damayanti (Jurnal Penelitian Pendidikan IPA, 2025)
The scientific-based discovery learning model encourages students to actively search for and construct concepts independently, thereby improving their critical thinking skills. Field observations show that students' critical thinking abilities in the Plant Development Structure 2 (SPT 2) course remain low. This study aims to determine the effect of the scientific-based discovery learning model on the critical thinking abilities of biology education students at the University of West Sulawesi. Using a true experimental design with randomly assigned control and experimental groups, data were collected through a critical thinking ability test. Statistical analysis using an independent samples t-test shows a significant difference between the two groups. This study finds that scientific-based discovery learning significantly improves students’ critical thinking abilities, with the experimental group achieving higher scores and a very large effect size.